Zinc ion battery negative electrode, preparation method thereof and zinc ion battery

By forming a solid electrolyte interface layer rich in ZnF2 and other inorganic substances on the surface of zinc foil, the corrosion and dendritic growth of the negative electrode of zinc ion battery are solved, the cycle life and Coulomb efficiency are improved, and the commercial application of zinc ion battery is promoted.

CN119230703AActive Publication Date: 2024-12-31HUNAN AGRI UNIV
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411498150.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-25
Publication Date
2024-12-31
Estimated Expiration
2044-10-25

AI Technical Summary

Technical Problem

The negative electrode of zinc ion battery has problems such as corrosion, hydrogen evolution reaction, interface parasitic reaction and dendritic growth during the galvanizing/stripping process, resulting in low utilization, low Coulomb efficiency and short cycle life, limiting its commercial applications.

Method used

The solid electrolyte interface layer rich in ZnF2 and other inorganic substances is formed on the surface of the zinc foil. A protective layer is formed on the surface of the zinc foil by modifiers such as ammonium hexafluoro silicate, which hinders the occurrence of side reactions and accelerates protection through heat treatment or power-on treatment. Formation of layers.

Benefits of technology

It significantly improves the cycle life and Coulomb efficiency of zinc ion batteries, extends the stability of the battery, and promotes its application in the field of large-scale energy storage.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119230703A_ABST
    Figure CN119230703A_ABST
Patent Text Reader

Abstract

The invention discloses a zinc ion battery negative electrode, a preparation method thereof and a zinc ion battery. The zinc ion battery negative electrode is obtained by performing heat treatment on zinc foil in a modifier, the modifier is any one or a combination of at least two of ammonium hexafluorosilicate, ammonium hexafluorophosphate, ammonium fluoride, potassium hexafluorosilicate, sodium hexafluorosilicate, sodium hexafluorophosphate and potassium hexafluorophosphate; the heat treatment temperature is 60-80 DEG C. The modifier can form a protective layer on the surface of the zinc foil, corrosion can be inhibited, zinc ion transmission and deposition can be regulated and controlled, and the electrochemical performance of the zinc ion battery can be remarkably improved. And the prepared zinc ion battery has excellent cycle life, long cycle stability and high specific discharge capacity.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of batteries, and more specifically, relates to a zinc ion battery negative electrode and a preparation method thereof, and a zinc ion battery. Background Art

[0002] With the rapid development of the global economy, serious problems such as fossil fuel shortage and worsening environmental pollution have become increasingly prominent. Vigorously developing green energy storage systems to replace or partially replace traditional fossil fuels has become the current research mainstream. Metal ion batteries, such as (lithium, sodium, zinc, magnesium, calcium and aluminum), have received widespread attention in the field of electrochemical storage systems. In particular, lithium-ion batteries are widely used as portable energy storage devices in the market due to their high energy density, light weight, negligible memory effect and long cycle life. However, lithium-ion batteries are high in cost and have safety issues caused by thermal runaway of organic electrolytes. In contrast, aqueous zinc-ion batteries are regarded as a promising large-scale energy storage technology due to their inherent safety and the unique advantages of zinc metal anodes. These include high theoretical capacity (820mAh g -1 ) and low redox potential (-0.76 V vs. SHE). Unfortunately, commercial applications are hampered by corrosion, hydrogen evolution reaction, interfacial parasitic reactions, and dendrite growth of the Zn anode during the zinc plating / stripping process, resulting in low utilization, low Coulombic efficiency, and short cycle life. Therefore, developing effective strategies to address these issues is crucial for the practical application of aqueous Zn-ion batteries.

[0003] In order to solve the above problems of zinc metal, researchers have done a lot of work at this stage, including interface modification, electrolyte optimization and diaphragm modification. Due to the characteristics of zinc-ion batteries (directly using zinc foil as the negative electrode), it is a simple and effective method to directly modify the zinc negative electrode to obtain a zinc-ion battery with long life and high coulombic efficiency. At present, the modification of the zinc negative electrode is usually to form a protective layer on the zinc surface with metal oxides and / or polymers, and the preparation process is relatively cumbersome. Therefore, studying a preparation process for the simple modification of the negative electrode of zinc-ion batteries is of great significance for its practical application. Summary of the invention

[0004] The purpose of the present invention is to provide a zinc ion battery negative electrode and a preparation method thereof and a zinc ion battery. The modified negative electrode can slow down corrosion, induce uniform deposition of zinc ions and inhibit the growth of zinc dendrites. The assembled zinc ion battery has excellent cycle life, long cycle stability and better coulombic efficiency.

[0005] To achieve the above object, the present invention provides the following technical solutions:

[0006] A negative electrode for a zinc ion battery, wherein the negative electrode is obtained by forming a protective layer on a zinc foil in a modifier solution; the modifier is any one of ammonium hexafluorosilicate, ammonium hexafluorophosphate, ammonium fluoride, potassium hexafluorosilicate, sodium hexafluorosilicate, sodium hexafluorophosphate, and potassium hexafluorophosphate, or a combination of at least two thereof

[0007] In the present invention, the modifier forms a solid electrolyte interface layer rich in ZnF2 and other inorganic substances on the surface of the zinc foil as a protective layer, thereby improving battery performance, hindering the occurrence of side reactions, and extending the battery cycle life.

[0008] Furthermore, the zinc foil can form a protective layer more quickly by heat treatment or electrical treatment in a modifier solution; the heat treatment temperature is 60-80°C.

[0009] The current and voltage of the energization treatment in the present invention are not limited, as long as a solid electrolyte interface layer rich in ZnF2 and other inorganic substances can be formed on the zinc foil. In some embodiments, a modifier can also be added to the electrolyte to form a protective layer on the surface of the zinc negative electrode during the operation of the battery.

[0010] Furthermore, the modifier is ammonium hexafluorosilicate.

[0011] Furthermore, the zinc foil has a thickness of 10-100 μm.

[0012] Further, the solvent of the modifier solution includes any one or a combination of at least two of deionized water, ethylene carbonate, acetonitrile, trimethyl phosphate, triethyl phosphate, carbonate methyl propionate, ethyl propionate, ethyl acetate, ethyl methyl carbonate, methyl formate, propylene carbonate, methyl acetate, triethylene glycol dimethyl ether or dimethyl sulfoxide, preferably water.

[0013] Furthermore, the content of the modifier in the modifier solution is 0.5-10 wt %.

[0014] The above-mentioned method for preparing the negative electrode of the zinc ion battery comprises the following steps: placing a zinc foil in a modifier solution to form a protective layer, wherein the modifier is any one of ammonium hexafluorosilicate, ammonium hexafluorophosphate, ammonium fluoride, potassium hexafluorosilicate, sodium hexafluorosilicate, sodium hexafluorophosphate, and potassium hexafluorophosphate, or a combination of at least two thereof.

[0015] A zinc ion battery comprises the above-mentioned negative electrode, electrolyte and positive electrode.

[0016] In the present invention, the type of zinc ion battery is not limited, and it can be an aqueous zinc ion battery, which includes a positive electrode sheet, the above-mentioned negative electrode, a separator and an electrolyte. Among them, the positive electrode is vanadium pentoxide or vanadium oxyhydroxide and other vanadium, manganese oxide positive electrode materials, the separator is a glass fiber membrane, and the electrolyte is a 2mol / LZnSO4 solution.

[0017] In the present invention, the zinc ion battery can also be a zinc symmetric battery, wherein the positive electrode and the negative electrode are both the negative electrode mentioned above.

[0018] Compared with the prior art, the present invention has the following beneficial effects:

[0019] The zinc ion battery negative electrode of the present invention has extremely high stability, and the protective layer formed on the surface of the zinc foil can inhibit the corrosion of zinc metal, reduce by-products, and extend the cycle life of the zinc ion battery, which is of great significance for promoting its application in the field of large-scale energy storage. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 1 This is the SEM of the zinc negative electrode prepared in Example 1 of the present invention.

[0021] Figure 2 It is a rate cycle performance test diagram of the zinc symmetric battery assembled with the zinc negative electrode prepared in Example 1 of the present invention and Comparative Example 1.

[0022] Figure 3 1 is a coulombic efficiency diagram of a half-cell assembled with the zinc negative electrode prepared in Example 1 of the present invention and Comparative Example 1.

[0023] Figure 4 It is a rate cycle performance test chart of the full battery assembled with the zinc negative electrode prepared in Example 1 of the present invention and Comparative Example 1.

[0024] Figure 5 It is a coulombic efficiency diagram of the assembled half-cell of the zinc negative electrode prepared in Example 5 of the present invention and Comparative Example 1. DETAILED DESCRIPTION

[0025] To make the purpose, technical scheme and advantages of the present invention clearer, the present invention will be described in further detail below in conjunction with embodiment, but the embodiments of the present invention are not limited thereto. Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those generally understood by the technicians belonging to the technical field of the present invention. The terms used in the specification of the present invention herein are only for the purpose of describing specific embodiments, and are not intended to limit the present invention. It should be noted that, unless otherwise specified, the reagents used in the present embodiment, etc. are all common commercial products.

[0026] Example 1

[0027] A zinc negative electrode heat-treated with ammonium hexafluorosilicate, the preparation method of which comprises the following steps:

[0028] Add 3g of ammonium hexafluorosilicate into deionized water to prepare a 300ml solution, then ultrasonically degas at room temperature to obtain a 1wt% ammonium hexafluorosilicate aqueous solution. A 100μm thick zinc foil was polished with 500-mesh and 2000-mesh sandpapers and cleaned with alcohol, then placed in the 1wt% ammonium hexafluorosilicate aqueous solution, ultrasonically degassed for 15S, then placed in a constant temperature oil bath at 60°C for 1min, taken out, rinsed with deionized water, and dried under an infrared lamp for 1h, then transferred to a vacuum drying oven overnight, taken out and cut into discs for later use. Figure 1 As shown in the SEM image, under the action of ammonium hexafluorosilicate, an artificial solid electrolyte interface layer of about 4μm is evenly formed on the zinc negative electrode.

[0029] Example 2

[0030] Compared with Example 1, the difference is that the modified zinc foil treated in an oil bath at 60° C. for 5 min is prepared.

[0031] Example 3

[0032] Compared with Example 1, the difference is that 6 g of ammonium hexafluorosilicate is added into deionized water to prepare 300 ml of solution, and the modified zinc foil heat-treated with 2 wt % ammonium hexafluorosilicate aqueous solution is prepared.

[0033] Example 4

[0034] Compared with Example 1, the difference is that the zinc foil is placed in a constant temperature oil bath and treated at 80°C for 1 min to prepare a modified zinc foil under 80°C heat treatment conditions.

[0035] Example 5

[0036] 6g of ammonium hexafluorosilicate was added as an additive to 300ml of 2M ZnSO4 electrolyte. A 100μm thick zinc foil was polished with 500-mesh and 2000-mesh sandpapers and cleaned with alcohol. It was used as the positive and negative electrodes. After power was applied for 1min, a zinc negative electrode with a protective layer was obtained.

[0037] Comparative Example 1

[0038] Compared with Example 1, the difference is that the zinc foil is not heat-treated with an aqueous solution of ammonium hexafluorosilicate, and an untreated zinc foil is prepared.

[0039] Performance Testing

[0040] The assembly of aqueous zinc-ion batteries follows the following assembly order: positive electrode shell, positive electrode material, separator, electrolyte, negative electrode and negative electrode shell. For zinc symmetric batteries, the electrodes on both sides of the separator are treated zinc foil; for Zn / / VOOH batteries, the positive electrode material is VOOH, the negative electrode is zinc foil heat-treated with 1% ammonium hexafluorosilicate aqueous solution, and the battery electrolyte is 180μL.

[0041] Figure 2 The zinc symmetric battery assembled with the zinc negative electrode prepared in Example 1 and Comparative Example 1 was shown to have a high conductivity at 0.2, 0.5, 1, 2, 3, 5, and 10 mA cm -2 The current density and 1 mAh cm -2 In Example 1, the limiting current of the zinc symmetric battery can reach 10 mA cm -2 , and the battery as a whole exhibits a stable voltage curve. In Comparative Example 1, at 2 mA cm -2 Current density and 1mAh cm -2 Under the conditions of the deposition surface capacity test, the zinc symmetric battery has already short-circuited and exhibited an unstable voltage curve. This further demonstrates that the zinc electrode obtained by heat treatment with ammonium hexafluorosilicate can effectively increase the rate cycling performance of aqueous zinc ion batteries.

[0042] Figure 3 The zinc-copper half-cell assembled with the zinc negative electrode prepared in Example 1 and Comparative Example 1 was charged at a current density of 1 mA cm -2 and an area capacity of 1 mAh cm -2 From the coulomb efficiency diagram under the test conditions, analysis of the results of Example 1 and Comparative Example 1 shows that the zinc electrode obtained by heat treatment with ammonium hexafluorosilicate has a higher coulomb efficiency than the blank zinc foil, which further illustrates that the zinc electrode obtained by heat treatment with ammonium hexafluorosilicate can effectively reduce the side reactions of the zinc ion battery and greatly extend the cycle life of the zinc ion battery.

[0043] Figure 4 The results show that the aqueous zinc ion full battery prepared by using Example 1 and Comparative Example 1 as the negative electrode and VOOH as the positive electrode has a high conductivity at 0.1, 0.2, 0.3, 0.5, 1, 2, 3, and 5 Ag. -1 The rate cycling performance at a current density of . It can be clearly observed from the figure that the whole battery assembled with the zinc negative electrode obtained by heat treatment with ammonium hexafluorosilicate has a higher discharge specific capacity.

[0044] Figure 5 The zinc-copper half-cell assembled using the electrolyte prepared in Example 5 or Comparative Example 1 (using 2M ZnSO4 as the electrolyte) at a current density of 1 mA cm -2 and an area capacity of 1 mAh cm -2The coulomb efficiency diagram under the test conditions shows that the results of Example 5 and Comparative Example 1 are analyzed, and it can be seen that the electrolyte with the addition of ammonium hexafluorosilicate has a higher coulomb efficiency and a longer cycle life than the 2M ZnSO4 electrolyte. This further illustrates that the electrolyte with the addition of ammonium hexafluorosilicate forms a protective layer on the zinc negative electrode under the action of the electric field, which can effectively reduce the side reactions of the zinc ion battery and greatly extend the cycle life of the zinc ion battery.

[0045] The above-mentioned embodiments only express several implementation methods of the present invention, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, and these all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.

Claims

1. A zinc ion battery negative electrode, characterized in that The negative electrode is obtained by forming a protective layer on zinc foil in a modifier solution; the modifier is any one of ammonium hexafluorosilicate, ammonium hexafluorophosphate, ammonium fluoride, potassium hexafluorosilicate, sodium hexafluorosilicate, sodium hexafluorophosphate, and potassium hexafluorophosphate, or a combination of at least two thereof.

2. The negative electrode according to claim 1, characterized in that It also includes heat treatment or electrical treatment.

3. The negative electrode according to claim 2, characterized in that The heat treatment temperature is 60-80°C.

4. The negative electrode according to claim 1, characterized in that The modifier is ammonium hexafluorosilicate.

5. The negative electrode according to claim 1, characterized in that The solvent of the modifier solution includes any one of deionized water, ethylene carbonate, acetonitrile, trimethyl phosphate, triethyl phosphate, carbonate methyl propionate, ethyl propionate, ethyl acetate, ethyl methyl carbonate, methyl formate, propylene carbonate, methyl acetate, triethylene glycol dimethyl ether or dimethyl sulfoxide, or a combination of at least two thereof.

6. The negative electrode according to claim 1, characterized in that The content of the modifier in the modifier solution is 0.5-10 wt %.

7. The method for preparing the negative electrode of a zinc ion battery according to any one of claims 1 to 6, characterized in that: The method comprises the following steps: placing the zinc foil in a modifier solution to form a protective layer, wherein the modifier is any one of ammonium hexafluorosilicate, ammonium hexafluorophosphate, ammonium fluoride, potassium hexafluorosilicate, sodium hexafluorosilicate, sodium hexafluorophosphate and potassium hexafluorophosphate, or a combination of at least two of the modifier.

8. The preparation method according to claim 7, characterized in that: The treatment temperature is 60°C.

9. A zinc ion battery, characterized in that: The negative electrode comprises the negative electrode as described in any one of claims 1 to 6.

Citation Information

Patent Citations

  • Zn-coated ZnF2 electrode material with three-dimensional network structure as well as preparation method and application of Zn-coated ZnF2 electrode material

    CN113140718A

  • Method for in-situ construction of artificial interface layer of zinc negative electrode through simple soaking method

    CN115224271A

  • Zinc tungstate coating modified zinc negative electrode and preparation method and application thereof

    CN117995972A

  • Negative electrode material for zinc-ion battery, and preparation method therefor and use thereof

    WO2024109903A1